Tolerance of Electromagnetic Relay to Voltage Sags and Short Interruptions - Zhang, Huaying; Wang, Qing; You, Yihong (Frontiers in Energy Research, 2021)
This paper studies the tolerance of electromagnetic relay (EMR) under voltage sag and short interruptions on the basis of response mechanism analysis and the extensive tests. First, it introduces the structure of EMR and proposes response mechanism of EMR under voltage sag. Then, a detailed test plan is presented, including the information of test platform, testing condition, EMRs used in test, list of test, test procedure, and the measured waveforms. Magnitude and duration of the sags are not only the characteristics to be considered to investigate EMR’s tolerance. The other factors, which may have significance influence on tolerance of EMR, are considered here, including point-on-wave (POW), phase angle jump (PAJ), harmonic, magnitude variation in pre- and post-sag segments, two-stage sag, and slow recovery sag. Extensive tests results are presented in the form of voltage-tolerance curves (VTCs). Besides magnitude and duration, POW, PAJ, and two-stage sag have a significant influence on the tolerance of EMR. Other factors only have a tiny impact on the tolerance of EMR. The results show that the magnitude tolerance of EMR is 48–74% of Unom, and duration tolerance is 5–28 ms; they are useful for the technical assessment of EMR’s tolerance to voltage sags and short interruptions, and for the economic assessment of the industry process trip due to its disengagement. Test results also benefit for choosing proper EMR and mitigation device in the complicated operating environment.